Analisis Pengaruh Jumlah Penduduk, Pengangguran dan Inflasi terhadap Pertumbuhan Ekonomi di Provinsi Kalimantan Tengah - Kezia Tamba; Alexandra Hukom (Universitas 17 Agustus 1945 Semarang, 2024)
Economic growth is a top priority for every country. Economic growth is used as an important indicator to assess economic performance. Population growth, unemployment rate, and inflation rate are considered important factors that influence economic growth. This research aims to analyze the influence of population, unemployment and inflation on economic growth in Central Kalimantan Province. The Vector Error Correction Model (VECM) method is used to analyze short-term and long-term relationships between these variables. The research results show that in the short term, inflation, unemployment and population do not have a significant effect on Gross Regional Domestic Product (GRDP). However, in the long term, only unemployment and population do not show a significant influence on GRDP. This research contributes to understanding the dynamics of economic growth and provides insight for policy makers in Central Kalimantan Province to formulate effective strategies for sustainable development.